The foam roll as a tool to improve hamstring flexibility - Junker, D. H.; Stöggl, T. L. (The Journal of Strength and Conditioning Research, 2015)
Although foam rolling is a common myofascial therapy used to increase range of motion (ROM), research is limited on the effectiveness of foam rolling on soft tissue extensibility. The aim of this study was to determine the effect of a 4-week training period of the foam roll method on hamstring flexibility. Furthermore, the study was designed to compare the effectiveness of the foam roll myofascial release with a conventional contract-relax proprioceptive neuromuscular facilitation (PNF) stretching method and a control group. Forty healthy males (age: 17-47 years) were randomly assigned to a foam roll group (FOAM, n = 13), a contract-relax PNF stretching group (CRPNF, n = 14), or a control group (CG, n = 13). The FOAM group massaged their hamstring muscles with the foam roll 3 times per week for 4 weeks (12 training sessions). The CRPNF group was assigned to 12 sessions of contract-relax PNF stretching. The CG underwent no intervention. Hamstring flexibility (ROM) was measured by a stand-and-reach test before and after the intervention period. Two-way repeated-measures analysis of variance showed a significant global time effect (p < 0.001) and an interaction effect for time × treatment (p = 0.004), demonstrating greater improvements in the FOAM and CRPNF compared with the CG, but no difference between the former. Delta changes from baseline to postintervention in ROM were not related to baseline ROM. The foam roll can be seen as an effective tool to increase hamstring flexibility within 4 weeks. The effects are comparable with the scientifically proven contract-relax PNF stretching method.